Prarancangan Pabrik Metil Klorida Dengan Proses Hidroklorinasi Metanol Kapasitas 100.000 Ton/Tahun - Saptyana, Eka; , Hamid Abdillah, S.T., M.T; , Eni Budiyati, S.T., M.Eng (2017)
The methyl chloride plant is designed with a capacity of 100.000 tons / year which operates 330 days per year and is continuous. The plant is planned to be established in 2020 area of Cilegon, Banten. The selection of the venue is based on the provision of raw materials, transportation, labor, and marketing. Methyl chloride is widely used as raw material for methyl cellulose, buthyl rubber, and refrigerant. The largest use of world methyl chloride in 2011 was found in the silicone polymer industry of 84% of the total requirement. The need for methyl chloride in Indonesia is still large because it is still imported from abroad. Raw material for methyl chloride preparation is methanol and hydrochloric acid with the aid of silica gel alumina catalyst at temperature of 300 - 390 °C at 10 atm. The reaction run in non adiabatic non-isothermal fixed bed reactor with conversion in the reaction is 99% is exothermic, so Dowtherm A is required to keep the temperature stable. The phase that occurs is the gas phase. Preparation of methyl chloride there are some processes namely the preparation stage of raw materials, the stage of product formation, and the stage of purification and storage of products. The required methanol of 8.112,8002 kg/hour and the hydrochloric acid requirement of 27.932,7612 kg/hour. The process support units include water supply of 440.455,5127 kg/hr obtained from river water, saturated steam supply of 7.851,2503 kg/hour, compressed air requirement 13,2523 m3/hour, electricity requirement 2.015,8606 kW, obtained from PLN and generator set of 2600 kW as reserve, as much as 1.151,4919 liter per hour fuel. This methyl chloride plant is a limited liability company held by several shareholders. From the economic analysis to this factory shows Percent Return on Investment (ROI) that is 44,67%. Pay Out Time (POT) 1.83 years. Break Even Point (BEP) of 42,99% and Shut Down Point (SDP) of 22% and Internal Rate of Return (IRR) based on Discounted Cash Flow (DCF) of 24,64%. From feasibility analysis it can be concluded that this factory is feasible to be established. Keywords: methyl chloride, methyl chloride production, support unit, economic analysis.